Computational study of the effect of intake geometry on the performance of an internal combustion engine / Muhammad Arif Ab Hamid Pahmi ... [et al.] - Ab Hamid Pahmi, Muhammad Arif; Idres, Moumen; Mahamad Basri, Mahamad Hisyam; Che Mat, Sharzali (Universiti Teknologi MARA, Perlis, 2011)
Intake system is an important consideration in a study of engine induction system. In such way, numerous studies on the effect of intake system were carried in improving engine power. The present study deals with the effect of different intake configurations on a 4-stroke single cylinder engine in wide range engine speed. In order to study the intake geometry effect, four different intake configurations proposed by Mariucci (2006) were modeled and simulated using GT-Power software. At first, the computational model is compared to Mariucci’s experimental data for calibration. The study showed adding taper geometry exhibits a significant volumetric efficiency improvement 3% and performs 19.5 kW in brake power. For bell mouth design, maximum volumetric efficiency reduced in 4% but similar brake power of 19.5 kW is obtained. Furthermore, there is an acceptable match between simulation and experimental results for all intake configurations.